Republished: Transradial approach in the treatment of a sacral dural arteriovenous fistula: a technical note. (22nd May 2019) - Orru, Emanuele; Tsang, Chun On Anderson; Klostranec, Jesse M; Pereira, Vitor M
Abstract : Sacral dural arteriovenous fistulas (SDAVFs) are rare, constituting no more than 10% of all spinal dural fistulas. They are most commonly fed by the lateral sacral artery (LSA), a branch of the internal iliac artery (IIA). Catheterization of this vessel requires either a crossover at the aortic bifurcation in cases of right femoral access or retrograde catheterization from the ipsilateral common femoral artery. We present the case of a 79-year-old man with tethered cord syndrome and a symptomatic SDAVF fed by two feeders from the left LSA. Spinal diagnostic angiography was made exceptionally challenging by an aorto-bi-iliac endograft, and selective catheterization of the left IIA was not possible. The patient could not undergo surgery due to multiple comorbidities, therefore embolization was considered the best approach. The procedure was carried out through a transradial access (TRA) with Onyx and n-butyl cyanoacrylate. The SDAVF was successfully treated and the patient made a full neurological recovery.